KAJIAN RANTAI NILAI PRODUK JERUK KEPROK SOE KABUPATEN TIMOR TENGAH SELATAN - Gregorius G Batafor; Yason Edison Benu (Partner, 2019)
Soe tangerine product value chain study becomes important to answer the problem of scarcity of product supply when not during the harvest season. The problem of shrinkage and damage to agricultural products including Soe tangerines is a classic problem that is very difficult for any party to overcome. In general, one of the objectives of studying the value chain is to be able to give an idea and determine which actors are right to apply storage technology that can answer the problem of shrinkage and damage to agricultural products including Soe tangerines. Specifically in this study, the objective to be achieved is to analyze the value chain and assess the added value that has occurred along the distribution chain of Soe tangerine products. The research methodology was conducted using descriptive questionnaires, value chain analysis was carried out starting from farmers, collectors and retailers in several community markets in the city of Kupang, while the value added analysis used the Hayami method. The results of the value chain analysis show that the level of profit for collectors is IDR 5,306 per kg, and for retailers it reaches IDR 10,806 per kg, whereas when compared to the profits of farmers as producers it is only IDR 1,806 per kg. If the difference in profit is calculated between each actor in the Soe tangerine product distribution chain, the farmers who are producers and upstream of the product only receive an added value of IDR 2,250 per kg, while the collecting traders receive an added value of IDR 5,750 per kg and retailers receive added value of IDR 11,250 per kg. The resulting RC ratio is 1.14 at the farmer level, 1.31 at the collector trader level and 1.45 at the retailer trader level. Thus it can be concluded that the tangerine citrus farmers benefit and the added value is lower than the traders and retailers in the people's markets.